2001
DOI: 10.1128/jvi.75.17.7913-7924.2001
|View full text |Cite
|
Sign up to set email alerts
|

Multimerization of Human Immunodeficiency Virus Type 1 Gag Promotes Its Localization to Barges, Raft-Like Membrane Microdomains

Abstract: The Gag polyprotein of human immunodeficiency virus type 1 (HIV-1) organizes the assembly of nascent virions at the plasma membrane of infected cells. Here we demonstrate that a population of Gag is present in distinct raft-like membrane microdomains that we have termed "barges." Barges have a higher density than standard rafts, most likely due to the presence of oligomeric Gag-Gag assembly complexes. The regions of the Gag protein responsible for barge targeting were mapped by examining the flotation behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
245
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(261 citation statements)
references
References 71 publications
16
245
0
Order By: Relevance
“…This method uses Optiprep (Iodixanol) (Axis-Shield, Norton, MA) gradients to monitor raft associated and soluble proteins derived from non-ionic detergent treated cell lysates [48]. Decreased palmitoylation has been shown to lead to decreased lipid raft association.…”
Section: Assessing the Functional Significance Of Altered Protein Palmentioning
confidence: 99%
“…This method uses Optiprep (Iodixanol) (Axis-Shield, Norton, MA) gradients to monitor raft associated and soluble proteins derived from non-ionic detergent treated cell lysates [48]. Decreased palmitoylation has been shown to lead to decreased lipid raft association.…”
Section: Assessing the Functional Significance Of Altered Protein Palmentioning
confidence: 99%
“…The Triton X-100-extractability assay, while widespread, is not used with sufficient uniformity that comparison of results from different laboratories is straightforward. In the case of HIV there is evidence that the coarseness of commonly used density gradients disguises the fact that Gag-membrane complexes float at a slightly higher density than conventional rafts (Lindwasser & Resh, 2001). Other combinations of detergent and temperature can be used to isolate raft-like membrane domains, which may have different compositions to those preserved in Triton X-100 at 4˚C (Roper et al, 2000).…”
Section: Evidence For Rafts In Virus Assemblymentioning
confidence: 99%
“…Rousso and colleagues observed that insolubility in cold Triton X-100 was dependent on the palmitoylation of at least one of the two cytoplasmic palmitoylation sites. Lindwasser & Resh (2001) examined the flotation of Gag on multiple-step Optiprep gradients and found that while 6-8 % of Gag floats in the raft fraction (marked by GM1 and caveolin-1), about 30 % of Gag was found at a slightly higher density. A reduction in Gag multimerization relocates some of this Gag to the raft fraction.…”
Section: Retrovirusesmentioning
confidence: 99%
“…Interaction of Gag proteins with the plasma membrane and membrane rafts may be enhanced or stabilized by lower-ordered Gag multimerization, but not required for higher-order Gag multimerization. The role of membrane rafts in enhancement of Gag-Gag interaction is not clear [165]. The viral surface glycoprotein complex (gp120 and gp41) is incorporated into the HIV-1 envelope together with membrane rafts by interactions of Gag protein with the cytoplasmic tail of gp41, which stabilizes the gp120-gp41 interaction.…”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
“…The role of membrane rafts in the assembly and budding of enveloped viruses has been investigated for influenza virus [59,63,[150][151][152][153][154][155][156][157][158][159][160], HIV-1 [63,[161][162][163][164][165][166][167][168][169][170][171][172][173], HTLV-1 [174], measles virus (Paramyxoviridae) [63,175,176], Sendai virus [Paramyxoviridae] [177,178], Newcastle disease virus (NDV; Paramyxoviridae) [179,180], RSV [147,148,[181][182][183][184], HSV [185,186], murine cytomegalovirus (MCMV; Herpesviridae) [187], Ebola virus [70,188], Marburg virus [70], and vesicular stomatitis virus (VSV; Rhabdoviridae) …”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%